Prevalence of Dental Anomalies among Schools Children in Sana'a City, Yemen - Al-Jawfi, Khaled A.; Ba-Salama, Mohammed A. (ARC Publications, 2016)
Objective: This study was designed to determine the relation of gender and systemic causes with dental anomalies. Methods: This study was conducted on (1000) of schools children,(500) boys and (500) girls with an age ranged from 4-12 years. The sample was collected from five private and four public schools at Sana'a city, Yemen. Children were examined at schools, under natural day light with a disposable mouth mirrors, using gloves and gauze pads. Results: Enamel hypoplasia (2.8%) was the most prevalent dental anomalies, followed by enamel hypocalcification (2.6%), then microdontia (0.5%), after that macrodontia and hypodontia (0.4%), then supernumerary teeth and dental transposition (0.3%), and finally dental fusion and gemination (0.2%). Conclusion: The frequency of dental anomalies among schools children was in boys more than girls. Enamel hypoplasia was the commonest dental anomaly, while the lowest dental anomalies were dental fusion and gemination.